Pemeriksaan Operasional Atas Aktivitas Pencatatan dan Pengendalian Persediaan Cafe Owl Ways di Pekanbaru - Timothy Tanujaya; Rimi Gusliana Mais (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Operational inspections have an important role to ensure that operational activities have run effectively and efficiently. Operational inspections also not only play a role in overcoming or repairing but also play a role in preventing these risks from occurring. The purpose of this study is to find out whether the policies and procedures for recording and controlling inventory implemented by Owl Ways Pekanbaru café have run effectively and efficiently. The research method used in this study is a descriptive study method. The data collection technique uses literature study data and field studies consisting of interviews, observations and company documents. The data that has been collected will then be analyzed. The object of research in this study is an operational inspection of inventory recording and control activities in an effort to improve the effectiveness and efficiency of inventory management of Owl Ways café in Pekanbaru. After an operational inspection, weaknesses were found in the Owl Ways café, namely inventory planning and control, inventory document recording procedures and the purchase of raw materials for supplies that are still inadequate